Down-regulation of the axonal PSA-NCAM expression coincides with the onset of myelination in the human fetal forebrain - Jakovcevski, Igor (2007)
The polysialic acid (PSA) modification of neural cell adhesion molecule, which reduces NCAM-mediated cell adhesion, is involved in several developmental processes, such as cell migration, axonal growth, pathfinding, and synaptic plasticity. It has been suggested that PSA-NCAM expression may inhibit myelination. To clarify the relationship between myelination and the expression of PSA-NCAM we systematically investigated its expression in the human forebrain from embryonic stage to midgestation (19–24 gestation weeks, gw). Immunofluorescence on cryosections showed that PSA-NCAM is expressed at the earliest stage studied (5.5 gw) in the primordial plexiform layer of the telencephalon, which mainly consists of neuronal processes. At midgestation, cortical axonal tracts in the emerging white matter were PSA-NCAM+, but they were not yet myelinated, based on the lack of myelin basic protein (MBP) immunoreaction. To follow the progression of myelination we developed organotypic slice cultures that included the subventricular and intermediate zones of the fetal forebrain. In freshly prepared slices, similar to cryosections, axonal tracts were PSA-NCAM+ but did not express MBP. After 5 days in culture there was a dramatic increase in MBP expression around the axons of the intermediate zone, which suggested the onset of myelination. Simultaneously with MBP up-regulation PSA-NCAM expression in axons was completely lost, as demonstrated both with immunofluorescence and Western blot analysis. These results support the idea that in the human fetal forebrain axonal PSA-NCAM expression is inversely related to primary myelination.